Quraish Shihab’s Quranic Exegesis on Interreligious Harmony and its Relevance to the Contemporary Western Hermeneutics - Abdulloh Fuadi (Ulumuna, 2021)
This paper discusses Quraish Shihab's Quranic Exegesis and its relevance to the hermeneutics framework of Martin Heidegger and Jurgen Habermas to trace Islamic moderation in Indonesia. The issue of interreligious harmony is the main theme of discussion. The type of library research is used in this research, where data is drawn from books, journal articles, and audio-video files. This paper is divided into three parts. The first part presents Quraish Shihab's qur’anic exegesis on inter-religious harmony, which was delivered at Lentera Hati and written in some of his works. The second part of the paper discusses Heidegger's facticital hermeneutics and Habermas's critical hermeneutics. The third part tries to integrate the qur’anic exegesis of Shihab with the hermeneutics concepts of Heidegger and Habermas. This effort of relevance is divided into two points of analysis. The first point juxtaposes Shihab and Heidegger in existentialist philosophical analysis. The second point juxtaposes Shihab and Habermas in intersubjective communication analysis. The paper shows the stringing network of meaning expressed by Quraish Shihab with contemporary western hermeneutics. Therefore, the paper argues that the religious thought of contemporary Indonesian exegete, M. Quraish Shihab, is relevant to the philosophical thoughts of contemporary philosophers, such as Heidegger and Habermas.